Emotional responses to motion sickness in autonomous driving - Silva, R. (2022)
In future autonomous cars, users, free from the primary task of driving, will have time and space to engage in other activities while traveling, such as reading a book, working on a laptop or watching a movie. Although the option for these activities are one of the great advantages of autonomous cars, this will also likely increase motion sickness (MS) inside the car. MS affects numerous individuals, and it occurs when the information received through the eyes differs from what is perceived by the body and the inner ear. Plus, MS can have an impact on the emotional component of the individuals experiencing it, making the experience of traveling in autonomous cars uncomfortable and difficult. Emotional design studies focus on the emotional response of individuals to a product or service. These studies typically employ self-report scales as assessment tools, such as SAM (Self-Assessment Manikin) and PrEmo (Product Emotion Measurement instrument). We present the first study measuring emotional responses to MS using both SAM and PrEmo scales. In our study, we induced MS by asking participants to watch a highly dynamic video of a first-person car trip. We also asked subjects to answer to SAM and PrEmo before and after the visualization of the video. Our results showed a change in the answers in time, that is, before vs. after the experience of MS. MS significantly altered individuals' emotional responses, worsening their condition. These results support the need for studies that reduce MS to improve the experience and well-being of individuals in autonomous cars.